Design and Implementation of an Automatic Fish Feeding System Based on Internet of Things (IoT) - Sopiandi Atmaja (Breakthroughs In Informatics, Networking, Algorithms, Research, And Yield (BINARY), 2026)
Manual feeding of ornamental fish often encounters obstacles such as delays, inaccurate portions, and dependence on human presence, which can affect fish health and water quality. To overcome these problems, this study designed an automatic fish feeder system based on the Internet of Things (IoT) using a prototype method with Arduino as the main controller, RTC as the scheduler, an ultrasonic sensor to monitor feed availability, a DHT11 sensor to measure temperature and humidity around the aquarium, a servo motor as the feed dispenser actuator, and a relay as an additional switch. The test results showed that the system was able to feed automatically three times a day according to the schedule, accurately detect feed availability, but still faced limitations in displaying temperature and humidity conditions. This system proved to improve maintenance efficiency, reduce feed waste, and help maintain the health of ornamental fish.